STRATEGI GURU DALAM MENGINTERNALISASI NILAI-NILAI KEARIFAN LOKAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Mohamad Aso Samsudin; Wedi Samsudi; Mahmudi Mahmudi; Hasanah Hasanah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
This study aims to describe the teacher's strategy and several factors that influence it in internalizing local wisdom values ​​in elementary school Islamic religious education subjects. This research is included in research that uses qualitative methods with a case study approach. Data collection techniques carried out by researchers include observation techniques, questionnaires, and interviews. Furthermore, the data that has been obtained is analyzed from the stages of reduction, presentation and verification. The results of this study indicate that the teacher's strategy for internalizing local wisdom values ​​in Islamic religious education learning is quite varied, from the teacher's strong understanding of local wisdom itself, identifying local wisdom around, determining learning objectives based on local wisdom and integrated teaching materials. local wisdom values. Factors supporting the realization of learning that internalizes local wisdom values ​​include clear government regulations, the wealth of local wisdom in Indonesia, adequate mileage, good school principal support, and compatibility between teaching materials and local wisdom values ​​in students. While the inhibiting factors were found to be the absence of a special budget, high entry fees for cultural heritage, weak parental support, and low understanding of local wisdom teachers in Indonesia.